Body composition in patients with thyroid disease using bioelectrical impedance analysis - Mohammad, Suhaili (2019)
Background: Thyroid hormone is an important hormone for body metabolism. Diseases affecting thyroid gland can cause either hyperthyroid or hypothyroid state. Both of these condition can alter body metabolism and causing changes in body composition. This study will compare body composition in 3 different thyroid state which were hyperthyroid, hypothyroid and euthyroid. Methods: This was a cross sectional study involving 47 patients who have been diagnosed with thyroid disease such as Grave‟s Disease, Multinodular Goitre (MNG), thyroiditis and congenital hypothyroid, age between 21 to 45 years old. Patients were divided into 3 groups which were hyperthyroid, hypothyroid and euthyroid group based on thyroid function test result. Body composition (body fat, body water and lean weight) were measured for each patients using Bioelectrical Impedance Analysis machine (Bodystat®Quadscan). Data was analyzed to compare body composition in all 3 groups. Results: A total number of 47 patients who had thyroid disease were analysed. Majority of the patients were female (85.1%) with mean age of 32.85 (±7.43) year old. 18 (38.3%) patients were in hyperthyroid group, 11 (23.4%) patients were in hypothyroid groups and 18 (38.3%) patients were in euthyroid groups. Body composition were measured and analysed between 3 groups. Total body fat was higher in hypothyroid group as compare to hyperthyroid group [F (2,44)=3.279, P=0.047]. Total body water (TBW) was also higher in hypothyroid group compare to hyperthyroid group with statistically significant differrence; P=0.05. Lean weight was also higher in hypothyroid group compare to hyperthroid group with statistically significant differrence; P=0.03. Conclusion: Thyroid hormone dysfunction cause significant changes in body composition in which hypothyroid state as compare to hyperthyroid patient cause higher total body fat, body water and lean weight.